Adsorption of Carbon Dioxide onto Activated Carbon Prepared from Coconut Shells - Pei-Hsing Huang; Hao-Hsiang Cheng; Sheau-Horng Lin (Journal of Chemistry)
This study presents the fabrication of high-quality activated carbon (AC) from discarded coconut shells. The effects of experimental parameters such as activation temperature and activation time on the basic characteristics of AC, including charcoal yield, ash content, pH value, Brunauer-Emmett-Teller (BET) specific surface area, total pore volume, and iodine adsorption, are investigated. The results indicate that as the activation temperature and activation time increase, the charcoal yield of the AC decreases. In contrast, iodine adsorption, ash content, pH value, and total pore volume increase with activation temperature. The AC sample activated at 1000°C for 120 min had the highest BET specific surface area and total pore volume and thus the best CO2 adsorption performance. This sample was compared with 30-mesh commercial AC. The results reveal that coconut-based AC has better instantaneous adsorption capabilities.